THE EFFECTIVENESS OF USING FLASHCARDS TOWARD THE STUDENT’S VOCABULARY MASTERY AT SMAN 15 MUARO JAMBI - Alfurqaan, Muhammad Naufal; Wennyta, Wennyta; Dinata, Ridho Praja (JELT: Journal of English Language Teaching, 2025)
This research aims to determine the effectiveness of using flashcards toward the student’s vocabulary mastery at SMAN 15 Muaro Jambi. This research used a quantitative research design with quasi-experimental approach, including quantitatively accepted pre-test and post-test. This research used total sampling namely population and sample of 34 people 17 students of class XI A were selected as control class and 17 students of class XI B were selected as the experimental class. The technique of collecting data is by multiple choice questions in this research, the data analysis technique was using the t test (independent sample T-test) on the SPSS for windows version 25 program. The results of this research indicate that students’ vocabulary mastery in text taught using the flashcards strategy post-test the average count (mean) is 71 that value higher than class using regular text book strategy in English subject namely post-test the average count (mean) is 63. And from data Analysis by independent sample T test tcount is 3.178 with the value Ttable (2.145) by it result then Ho is rejected and Ha is accepted. The result of this study showed an there is a effectiveness on the use of the flashcards strategy toward students’ vocabulary mastery, and it can be concluded that this flashcards strategy can applied in class that it helps a teacher increase students’ vocabulary mastery